Challenges and opportunities for perinatal health services in the COVID-19 pandemic: a qualitative study with perinatal healthcare professionals - Bettina Moltrecht; Simone de Cassan; Elizabeth Rapa; Jeffrey R. Hanna; Clare Law; Louise J. Dalton (BMC Health Services Research, 2022)
Abstract Background Perinatal healthcare professionals (PHCPs) provide essential support to all parents in the perinatal period, including young parents aged 16–24, who are at an increased risk of morbidity and mortality. Little is known about the impact of COVID-19 restrictions on the provision of perinatal services, and on perinatal healthcare professionals, caring for young parents in the UK. Methods A UK based qualitative study using semi-structured interviews with perinatal healthcare professionals (n = 17). Data were analysed using thematic analysis. Results Two themes were identified describing perinatal healthcare professionals’ perceptions of providing care to young parents during the pandemic. Perinatal healthcare professionals perceived that young parents’ needs were amplified by the pandemic and that pandemic-related changes to the service, such as the use of telemedicine to replace face-to-face interactions, did not manage to successfully mitigate the increased feelings of anxiety and isolation experienced by young parents. Concerns were raised by perinatal healthcare professionals that these changes reduced young parent’s access to vital support for themselves and their child and may contribute to exacerbating pre-existing inequalities. Conclusions This study provides insight into the impact of the COVID-19 pandemic on the provision of perinatal care to young parents. Perinatal mental health professionals felt these negative impacts could be overcome by using a blended approach of technology and face-to-face interactions allowing regular contact with young parents and facilitating the exchange of vital information, while maintaining access to opportunities for social interactions with other parents. Findings from this study could be used to future-proof services against further COVID-19 restrictions.